Blood Pressure in Women Taking Oral Contraceptives. Issue 5907 (23rd March 1974) - Weir, R. J.; Briggs, E.; Mack, A.; Naismith, L.; Taylor, L.; Wilson, E.
Abstract : A controlled prospective survey of women taking oestrogen-progestogen oral contraceptives showed increases in mean systolic and diastolic blood pressure of 14·2 mm Hg and 8·5 mm Hg respectively after four years. The largest increases in individual cases were 36 mm Hg systolic and 20 mm Hg diastolic. Blood pressure returned to pretreatment levels within three months after oral contraceptives had been stopped. These changes in blood pressure were unrelated to the progestogenic potencies of the preparations being taken.